The synergy between women’s empowerment groups and village libraries in fostering a rural information society in Cianjur, Jawa Barat - Saleha Rodiah; Henny Sri Mulyani Rohayati; Pandu Watu Alam; Siti Nurul Maryam Abdullah; Tita Nursari (Berkala Ilmu Perpustakaan dan Informasi, 2026)
Introduction. A concrete collaboration model is necessary to provide a practical reference for communities and libraries to play a role in building an information society. This study explores the synergy between women’s empowerment groups, particularly PEKKA and village libraries in building an information society to empower marginalized women, to improve access to information, and to enhance community literacy, especially in rural areas such as Sindanglaya Village, Cianjur. Research Methods. A qualitative case study approach was employed. Data were collected through interviews, observations, and document analysis with six informants selected using a purposive sampling technique. Data Analysis. The data were analyzed and triangulation was applied to ensure data validity. Results. The findings reveal that PEKKA initiated most collaborative programs while the village government provided financial and facility support. PEKKA members also contributed indirectly to the development and promotion of the Sindanglaya Village Library. The partnership increased women’s participation, confidence, and recognition in the community, as well as enhancing library usage and literacy awareness in the village. Conclusion. The effective synergy strengthens social inclusion, improves access to information, and fosters community empowerment. A partnership model is proposed to illustrate the roles, stages, and impacts of this collaboration in building an inclusive information society.